The philosophy of ethics in children's theater performances: a model example the play Shihab and the Secret of the Book - الطائي, علي جابر متعب علي الطائي (Basrah Arts Journal, 2026)
Ethics is one of the first issues that concerned philosophers, and a part of philosophical research has been devoted to it since the emergence of philosophy in the country of the Greeks, and the branch that is concerned with ethics, studying it and answering its questions is called (philosophy of ethics), and this branch is concerned with the search for the origin of ethics in the individual, how it is formed, what helps to consolidate and grow it, and in which aspect the ethical act is beneficial to the individual and his society. included two research topics, the first of which was the philosophy of morality cognitively, in which I studied the philosophy of morality from Greek and Muslim philosophers, and in the second research, I studied the philosophy of morality in theater performances, analyzing the research sample by relying on the descriptive method, and the sample is (the play Shihab and the Secret of the Book), and in the fourth chapter, the research results appeared And from her: (The director relied on scenographic elements to emphasize the philosophy of ethics, making the book of enormous, as he created music, songs, lighting, and costumes, according to the characteristics of the characters and their morals, and which emphasized the use of theatrical performance to present the philosophy of morality to the audience, and revealed the ways in which morality appeared in the research sample),then conclusions, recommendations, and suggestions, and concluded the research with a list of sources.